THE VATLY CHERENKOV DETECTOR AND ITS RESPONSE TO ELECTRONS AND MUONS - NGUYEN , THI THAO; PHAM , TUAN ANH; PIERRE , DARRIULAT; PHAM , NGOC DIEP; PHAM , NGOC DONG; NGUYEN , VAN HIEP; DO , THI HOAI; PHAM , THI TUYET NHUNG (Nuclear Science and Technology, 2012)
A replica of one of the 1660 Cherenkov detectors used in the ground array of the Pierre Auger Cosmic Ray Observatory in Argentina has been constructed on the roof of the VATLY astrophysics laboratory in Ha Noi (Viet Nam). I report on cosmic ray measurements made using this detector, including its response to relativistic feed-through muons. Particular emphasis is on event pairs occurring within a small time window. Data include time autocorrelation and charge spectra of the detected signals. They are analyzed in terms of muon decays in the water volume of the Cherenkov tank and of the probability to detect two secondaries of a same shower. The former provide useful information on the response of the detector to small signals. The latter measure the width of the lateral distribution functions of extensive air showers in the TeV region.